The impact of youth development program on rural livelihoods: A case of Fortune 40 young farmer incubation program in Bushbuckridge Municipality, South Africa - Khoza, Agreement; Mayekiso, Anele; Ledwaba, Lesetja Jacob; Belete, Abenet (Asian Journal of Agriculture and Rural Development, 2025)
Agricultural programs play a significant role in reducing poverty, improving livelihoods, and increasing productivity. This study analyzed how the Fortune 40 initiative, an agricultural program, impacted the rural livelihoods of youth in Bushbuckridge Local Municipality. Primary data was collected from 43 beneficiaries using a questionnaire through face-to-face interviews. A cross-sectional research design and a quantitative research approach were employed. Descriptive statistics, a Sustainable Livelihood Approach framework, and an Ordered Probit Model were used to analyze the data. Beneficiaries’ ages ranged from 22 to 38 years, with gender distribution being relatively balanced 53.5% female and 46.5% male. Challenges within the program included poor supervision, delays in input delivery, and theft. Overall, the Fortune 40 program had a moderate impact on rural livelihoods. The results indicated that factors such as age, household size, type of farming, access to credit, and land size influence the program’s impact. The study recommends fair land allocation for farming and improved access to credit, particularly for youth, agricultural graduates involved in farming, and aspiring farmers.